Decline and Devolution: The Sources of Strategic Military Retrenchment1. Issue 3 (7th July 2014) - Haynes, Kyle
<x xml:space="preserve">Abstract</x> This paper offers a theory of military retrenchment by states in relative decline. I argue that a declining state will choose to withdraw foreign military deployments and security commitments when there exists a suitable regional "successor" to which it can devolve its current responsibilities. The degree of a successor's suitability and the strategic importance of the region to the declining state interact to determine when and how rapidly retrenchment will occur. Importantly, this devolutionary model of retrenchment predicts significant variations in retrenchment patterns across a declining state's multiple regional commitments. It advances the literature by producing nuanced predictions of precisely where, when, and how quickly retrenchment will occur. This paper assesses the theory empirically through an examination of Great Britain's varying regional retrenchment strategies prior to World War I.